OTONOMI PENDIDIKAN DAN EKSISTENSI MADRASAH - Akmal Hawi (Conciencia, 2017)
The policy of regional autonomy has also implicated the education sector with the concept of decentralization of education, which aims to provide widespread authority to regulate and manage madrasah (local authorities) in the framework of improving the quality of education for all levels of society. Madrasah as one of the educational institutions that take shelter in the Department of Religion inevitably come into contact with the issue of educational autonomy. But the problem is whether the Department of Religion remains in the position of the autonomous rights holder for the entire education system in the madrasah or only limited to religious subjects only. A consistent, cautious but definite and nondisadvantageous attitude to the Department of Religion needs to be addressed in a special discussion.